2006
DOI: 10.1227/01.neu.0000204103.91793.77
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Cerebral Arteriovenous Malformation Embolization: Multivariate Analysis of Predictive Factors

Abstract: In a single-center, retrospective, nonrandomized study, 90.5% of patients had excellent or good outcomes after AVM embolization, with a complication rate lower than previously reported. Spetzler-Martin grade III to V and periprocedural hemorrhage were the most important predictive factors in determining outcome after embolization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
86
2
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(91 citation statements)
references
References 31 publications
1
86
2
2
Order By: Relevance
“…2,3,5,7,8 However, although the overall cure rates in these series have varied, none have demonstrated cure for most of their patients (Table). In addition, the permanent disabling morbidity or mortality rates have been higher than those in several recent large series using predominantly or exclusively n-BCA, [9][10][11][12] which have ranged from 1.6% to 6.5%. Embolization for cure was not the primary aim in most patients treated in these series.…”
mentioning
confidence: 72%
“…2,3,5,7,8 However, although the overall cure rates in these series have varied, none have demonstrated cure for most of their patients (Table). In addition, the permanent disabling morbidity or mortality rates have been higher than those in several recent large series using predominantly or exclusively n-BCA, [9][10][11][12] which have ranged from 1.6% to 6.5%. Embolization for cure was not the primary aim in most patients treated in these series.…”
mentioning
confidence: 72%
“…Additional treatment goals may include staged reduction of blood flow in an AVM by stepwise occlusion of deep feeding arteries that could provide dose planning to more critical locations (14,(17)(18)(19)22). …”
Section: █ Discussionmentioning
confidence: 99%
“…32 Morbidity rates reported later in the literature, in the era before introduction of Onyx, ranged between 5.6% and 14% concerning overall morbidity and 2%-12.8% concerning permanent morbidity, whereas mortality rates ranged between 0.6% and 3.7%. 3,6,9,[33][34][35][36][37][38][39] Several authors have reported the clinical outcome in patients after AVM embolization with Onyx. In their clinical article, Pérez-Higueras et al 14 reported an overall morbidomortality rate of 18% among 45 patients, whereas permanent morbidity was 15.5% and mortality, 2%.…”
Section: Discussionmentioning
confidence: 99%